2010
DOI: 10.1159/000313639
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Valganciclovir as Preemptive Therapy for Cytomegalovirus Infection Occurring in Allogeneic Stem Cell Transplant Recipients

Abstract: Few data are available to date on the dose of oral valganciclovir as cytomegalovirus (CMV) preemptive therapy in stem cell transplantation patients. This study aimed to evaluate the efficacy and safety of low-dose valganciclovir (900 mg/day) as preemptive treatment in allotransplanted recipients. Valganciclovir was used in 34 patients who underwent allogeneic stem cell transplantation for hematological malignancies at the dose of 900 mg oral administration/day (12 patients, group 1) or 1,800 mg oral administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…In this study, the incidences of toxicities including neutropenia and thrombocytopenia were higher in HSCT recipients who received standard-dose VGCV pre-emptive therapy than in HSCT recipients who received low-dose VGCV. Several studies have shown that the clinical efficacy of low-dose VGCV pre-emptive Non-hematologic 2 0 0.22 Table 2 therapy was equivalent to that of standard-dose VGCV for CMV infection; however, no significant difference in the frequency of toxicity between the 2 groups was reported (10,11). The subjects in our study included generally underweight Japanese patients compared to non-Asian patients, indicating the possibility that an excessive dose based on weight induced a high frequency of side effects in the standard-dose group in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the incidences of toxicities including neutropenia and thrombocytopenia were higher in HSCT recipients who received standard-dose VGCV pre-emptive therapy than in HSCT recipients who received low-dose VGCV. Several studies have shown that the clinical efficacy of low-dose VGCV pre-emptive Non-hematologic 2 0 0.22 Table 2 therapy was equivalent to that of standard-dose VGCV for CMV infection; however, no significant difference in the frequency of toxicity between the 2 groups was reported (10,11). The subjects in our study included generally underweight Japanese patients compared to non-Asian patients, indicating the possibility that an excessive dose based on weight induced a high frequency of side effects in the standard-dose group in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Los antivirales que pueden ser usados son ganciclovir iv (A1), y nuevas publicaciones también avalan el uso de valganciclovir oral en caso de que el paciente esté en condiciones de deglutir y no presente diarrea ni mucositis 26,27 . (Tabla 3.a).…”
Section: Tanto La Profilaxis Universal Como La Terapia Anticipada Sonunclassified
“… 22 Moreover, finally, the threshold used to start preemptive therapy shows an enormous variation from center to center (100, 200, 500, 600, 1000, 10,000, 50,000 copies/ml, to put some examples). 22 , 85 90 …”
Section: Introductionmentioning
confidence: 99%